(3GdTaG HJYQja Mbhb GdeUWaj (B( (3Udi Gddg Ydjg hSde (B)s - (3YjGV Hf ehSi Hf YjGV Hf YeQhf GdjMUHj GdSHJj, CHh GdaVd,J (B544 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdefaQO HGSeg GdCSei CeG HYO CTQb Gddg bdHi hbdHc HGfhGQ Gdjbjf s
(3BNQgG (B:s
(3dcfG bOefG ef HjGf eYLRI fHjfG Udi Gddg Ydjg hSde XghQgG eG jZfi Yf QchH HWhf gPg GdeSGdc hXghQgG hHGddg CSJYjf s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B99 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B16s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs